Association between PR interval prolongation and electro-anatomical substrate in patients with atrial fibrillation. - Katja Schumacher; Petra Büttner; Nikolaos Dagres; Philipp Sommer; Borislav Dinov; Gerhard Hindricks; Andreas Bollmann; Jelena Kornej (PLoS ONE, 2018)
BACKGROUND:Atrial fibrillation (AF) is the most common sustained arrhythmia in clinical routine. Left atrial (LA) electro-anatomical remodelling in AF patients indicates disease progression and is associated with poor therapeutic success. PR interval prolongation is associated with an increased risk for AF, however, the association between LA remodelling measured as low voltage areas (LVA) during catheter ablation and PR interval is unknown. The aim of this study was to investigate the association between PR interval prolongation and LVA in AF patients. METHODS:We studied 103 patients (62±12 years, 59% males, 34% persistent AF) undergoing first AF catheter ablation and presenting with sinus rhythm. PR interval prolongation was defined as PR >200ms and analysed in resting ECG before intervention. LVA were determined using high-density maps and defined as <0.5 mV. RESULTS:There were 24 patients (23%) with PR interval prolongation and 18 patients (17%) with LVA. There were significant correlations between PR prolongation with LVA, CHA2DS2-VASc score and eGFR (r2 = 0.230, 0.216, and 0.307, all p<0.05). PR interval prolongation (OR 3.450, p = 0.024), persistent AF (OR 5.391, p = 0.002), and LA size (OR 1.117, p = 0.018) were significant predictors for LVA, while age (OR 1.072, p = 0.005), LVA (OR 3.450 p = 0.024) and eGFR (OR 0.962, p = 0.004) were associated with PR interval prolongation. CONCLUSIONS:Beside persistent AF and LA size, PR interval prolongation might be useful for the prediction of electro-anatomical substrate in AF patients. Larger studies are needed to confirm these results.